TEACHER STRATEGIES IN EDUCATING STUDENTS' EMOTIONAL INTELLIGENCE - Esti Alemia Puspita; Fauzan Putraga Albahri (CV Naskah Aceh, 2022)
Emotional intelligence education is education to be able to recognize. Expressing and managing emotions, both their own emotions and the emotions of others. With constructive actions, which promote cooperation as a Team that refers to productivity and not to conflict. In this research the author explains the teacher's strategy in educating students' emotional intelligence. The aim of this research is to find out what strategies teachers use in educating students' emotional intelligence at Jaya Langsa High School and to find out the obstacles faced by teachers in educating students' emotional intelligence at Jaya Langsa High School. The research method for this research is descriptive, namely a study that discusses current problems using library research and field research, namely by observing interviews and questionnaires with a sample of 45 students at Jaya Langsa High School and the school principal and teachers. Based on the research results, a conclusion can be drawn that the teacher's strategy in educating students' emotional intelligence at Jaya Langsa High School is in the form of establishing discipline. Providing package books containing emotional intelligence and the implementation of extracurricular activities in the form of emotional mental strengthening through Scout activities and these activities take place together with teaching and learning process activities. through implementing special strategies by providing teaching guidance to teachers and creating special activities outside of school. The obstacles faced by teachers in implementing strategies for educating students' emotional intelligence are teachers' lack of understanding of the importance of emotional intelligence, teachers' lack of knowledge about specific strategies in educating students' emotional intelligence, and lack of media to help teachers to educate students' emotional intelligence, so it is hoped that Teachers should be able to deepen their knowledge of emotional intelligence in order to produce students who are not only intellectually intelligent but also emotionally intelligent.